Pengaruh Likuiditas, Pertumbuhan Penjualan, dan Struktur Aset terhadap Struktur Modal pada Perusahaan Sub Sektor Industri Barang yang Terdaftar di Bursa Efek Indonesia Periode 2020-2024 - Amalix Pajar; Novera Martilova (ARZUSIN, 2026)
Although capital structure is an important aspect of corporate financial management and various studies have examined the factors that influence it, research on the effects of liquidity, sales growth, and asset structure among goods industry subsector companies listed on the Indonesia Stock Exchange remains limited. This study aimed to analyze the effects of liquidity, sales growth, and asset structure on the capital structure of goods industry subsector companies listed on the Indonesia Stock Exchange during the 2020–2024 period. This study employed a quantitative approach with a causal design. The research sample consisted of eight companies selected through purposive sampling, resulting in 40 observational units. Secondary data in the form of annual financial statements were collected through the documentation method and analyzed using multiple linear regression with the assistance of IBM SPSS Statistics version 26. The results showed that, partially, liquidity had a significant effect on capital structure, whereas sales growth and asset structure had no significant effects. Simultaneously, liquidity, sales growth, and asset structure had a significant effect on capital structure. These findings reinforce the relevance of Pecking Order Theory, Trade-Off Theory, and Signaling Theory in explaining the factors that influence corporate financing decisions. This study confirms that liquidity is an important factor that must be considered in determining capital structure, whereas sales growth and asset structure need to be analyzed together with other financial factors. Theoretically, this study enriches the literature on the determinants of capital structure, whereas practically, its findings may serve as a consideration for corporate management, investors, and creditors in formulating more effective financing decisions. Future research is recommended to incorporate additional variables and broaden the research objects to obtain more comprehensive results.